2002
DOI: 10.1001/jama.288.21.2693
|View full text |Cite|
|
Sign up to set email alerts
|

Myocardial Perfusion Imaging for Evaluation and Triage of Patients With Suspected Acute Cardiac Ischemia

Abstract: Sestamibi perfusion imaging improves ED triage decision making for patients with symptoms suggestive of acute cardiac ischemia without obvious abnormalities on initial ECG. In this study, unnecessary hospitalizations were reduced among patients without acute ischemia, without reducing appropriate admission for patients with acute ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(42 citation statements)
references
References 26 publications
2
37
0
1
Order By: Relevance
“…So far, echocardiography is still the first-line imaging modality in triaging cardiac disorders due to its nearly universal availability, potential use at the bedside and low cost [8,9,10,11,12,19,20,21]. Beside its mainstream ability of determining global and regional LV function as well as valvular morphology and function in real-time within minutes, its diagnostic impact within the CPU setting can be further enhanced by, for example, strain, tissue-Doppler, perfusion or speckle-track analysis [22,23,24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…So far, echocardiography is still the first-line imaging modality in triaging cardiac disorders due to its nearly universal availability, potential use at the bedside and low cost [8,9,10,11,12,19,20,21]. Beside its mainstream ability of determining global and regional LV function as well as valvular morphology and function in real-time within minutes, its diagnostic impact within the CPU setting can be further enhanced by, for example, strain, tissue-Doppler, perfusion or speckle-track analysis [22,23,24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…The advantages of rest rMPI were confirmed by a large, prospective multicenter trial, which showed that with implementation there was a 10% absolute reduction of admissions for noncardiac chest pain. [30][31][32][33] Furthermore, multiple studies have shown that the negative predictive value of rest rMPI for ACS is 99% to 100%, which confirms that rest rMPI has the potential to safely reduce admissions for noncardiac chest pain. 34 Because perfusion defects on rMPI do not distinguish between acute ischemia, acute infarction, or previous infarction, there are several limitations to the usage of rest rMPI for the evaluation of ACS.…”
Section: What Is the Role For Cardiac Imaging In Recognition Of Acutementioning
confidence: 78%
“…Recently, a randomized controlled trial compared the usual evaluation strategy of patients with suspected acute cardiac ischemia with the addition of results from acute resting myocardial perfusion imaging using single-photon emission computed tomography. Such strategy allowed the attending physician to reduce unnecessary hospitalizations without reducing appropriate admissions of patients with acute ischemia [16].…”
Section: Discussionmentioning
confidence: 99%